2014
DOI: 10.1177/0162353214540824
|View full text |Cite
|
Sign up to set email alerts
|

The Role of E-Mentoring in Mathematically Gifted Students’ Academic Life

Abstract: This qualitative inquiry presents the case study of five gifted eighth-grade students who engaged in an e-mentoring project in mathematics. The study reported in this article investigated the role of e-mentoring in gifted students’ academic life. Three themes predominated in the collected data were (a) motivation, (b) effective communication and supportive interaction, and (c) practicing as professionals. The findings indicated that the students engaged with e-mentoring had high motivation and desire and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Research supports the benefits of this type of mentoring for gifted children. Mammadov and Topcu studied the effectiveness of pairing eighth‐grade students who were advanced in mathematics with an e‐mentor who provided challenging mathematics problems based in real‐world contexts—ones more complex than those found in mathematics books 20 . They found that benefits for students included increased motivation and self‐efficacy.…”
Section: A Developmental Stage Model Of Mentoringmentioning
confidence: 99%
“…Research supports the benefits of this type of mentoring for gifted children. Mammadov and Topcu studied the effectiveness of pairing eighth‐grade students who were advanced in mathematics with an e‐mentor who provided challenging mathematics problems based in real‐world contexts—ones more complex than those found in mathematics books 20 . They found that benefits for students included increased motivation and self‐efficacy.…”
Section: A Developmental Stage Model Of Mentoringmentioning
confidence: 99%
“…We also found that the success of collaboration in terms of the five elements of CL appears more possible in a synchronous environment than in an asynchronous environment (e.g. Mammadov & Topçu 2014).…”
Section: Resultsmentioning
confidence: 63%
“…The Gifted individuals, as defined by Hallahan (2009), mentioned in Mammadov & Topuc (2014): A group of individuals possess cognitive superiority, creativity, and motivation, which significantly set them apart from the vast majority of their age peers, and make it possible for them to contribute something of exceptional value to society The Gifted individuals procedurally: A group of individuals who were characterized by mental, psychological and social characteristics that made them surpass their peers and receive the admiration and appreciation of the Messenger of Allah (PBUH), and whose contemporaries attested to their talent and excellence. The Prophetic Sunnah, which stands for all recorded acts, speeches or endorsements Prophet Muhammad (PBUH).…”
Section: Terminology Of the Studymentioning
confidence: 99%